Transformation of the Indonesian Constitutional System Through Amendments to the 1945 Constitution - Rahaditya, R; Rachmat, Lidya Imelda; Sari, Raden Ajeng Diah Puspa; Nugroho, Yahya Abdi (CV. Rayyan Dwi Bharata, 2024)
The constitutional system is the rules that regulate how the government in a country is run so that the government can run well. In Indonesia the constitutional system is regulated by the constitution. The 1945 Constitution was ratified as a constitution on August 18 1945 and plays an important role in the implementation of the constitutional system in Indonesia. When talking about the 1945 Constitution, the thing that sticks is amendments. Amendments are activities carried out by authorized institutions to change or add provisions to the 1945 Constitution. Along with developments over time, the 1945 Constitution has also undergone amendments. Since 1945 until now, the 1945 Constitution has undergone 4 amendments, namely from 1999 to 2002. The amendments to the 1945 Constitution have had an impact on the constitutional system. Government power is not only concentrated in one or two state institutions, so that the balance of the ecosystem in government can survive and run with the implementation of democracy.